(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the effect of deep learning on students’ critical thinking skills in mathematics learning in grade XI high school. This study uses a quantitative approach with a quasi-experimental design involving one experimental class and one control class. Deep learning treatment was given to the experimental class, while the control class followed conventional learning. Data on critical thinking skills were collected through a validated posttest. Data analysis was performed using the Shapiro–Wilk test to test normality, the Levene test to test homogeneity, and the independent samples t-test to test the difference in means between the two groups. The results of the analysis showed a significance value of 0.000, which is less than 0.05, indicating a significant difference between the critical thinking skills of students in the experimental class and the control class. These findings indicate that deep learning has a positive and significant effect on improving students’ critical thinking skills in mathematics learning.